Book Reviews. Issue 1 (30th July 2019) - Matsumoto, Lila; Sengupta, Shalini
Abstract : Lila Matsumoto reviews Toward. Some. Air.: Remarks on Poetics, edited by Fred Wah and Amy De'Ath (2015); Shalini Sengupta reviews For the Future: Poems & Essays in Honour of J.H. Prynne on the Occasion of his 80th Birthday, edited by Ian Brinton (2016).